Seasonal Variation of Boron in Saline-Sodic Soils - Bandyopadhya, A K (Annals of Arid Zone, 2016)
Seasonal variation of boron in the saturation extract of highly saline-sodic soil profile has been reported. During the dry period, boron accumulated in the surface soil and decreased gradually with depth. Due to natural leaching with rain water boron as well as soluble salts leached downwards.